Intensive care scores predict outcomes in patients receiving cytoreductive surgery and hyperthermic intraperitoneal chemotherapy - Wimmer, Julia; Acs, Miklos; Bohus, Gyula; Hauer, Patricia; Müller, Veronika; Bogovic, Niklas; Kupke, Paul; Slowik, Przemyslaw; Schlitt, Hans J.; Hornung, Matthias; Werner, Jens M. (Frontiers in Surgery, 2025)
IntroductionSurgical management of patients with peritoneal surface malignancies (PSM) via multivisceral resection is associated with increased morbidity and mortality in the immediate postoperative period, rendering intensive care therapy critically important. We aimed to determine whether intensive care unit (ICU) course and scoring systems predict not only short-term but also long-term outcomes.MethodsWe retrospectively analyzed the medical records of all patients who underwent cytoreductive surgery (CRS) and hyperthermic intraperitoneal chemotherapy (HIPEC) for peritoneal surface malignancies (PSM) between 2008 and 2015 at a university cancer center. Upon postoperative ICU admission, Simplified Acute Physiology Score (SAPS II) and Sequential Organ Failure Assessment (SOFA) scores were recorded. Complications during the ICU stay and overall hospitalization were documented, and patients were followed according to a standardized protocol after discharge.ResultsA total of 251 patients were included. The mean Peritoneal Cancer Index (PCI) was 14 ± 9.1 and correlated significantly with both ICU stay duration (p = 0.002) and total hospital stay (p = 0.001). In-hospital mortality was 2%, and the reoperation rate was 16.7%. SOFA scores on the day of surgery, postoperative days 1, 2, and 7 demonstrated strong correlations with ICU length of stay (all p ≤ 0.001) and with overall hospital stay (p = 0.001 for the day of surgery and day 7; p ≤ 0.001 for days 1 and 2). In multivariate analysis, SOFA score on postoperative day 7 [hazard ratio (HR) 1.261; 95% confidence interval (CI) 1.120–1.421; p ≤ 0.001] and SAPS II on the day of surgery (HR 1.042; 95% CI 1.017–1.068; p ≤ 0.001) emerged as independent predictors of overall survival.DiscussionIn conclusion, SAPS II and SOFA scores not only predict ICU and hospital lengths of stay but also independently forecast overall survival in patients undergoing CRS and HIPEC for PSM.